COVID-19 Impacts and Adaptive Responses in Enugu Slums: Lessons for Urban Sustainability - John-Nsa, Chioma Agatha; Israel, Glory Chioma; Chukwurah, Gladys Ogochukwu; Enoguanbhor, Evidence Chinedu (Urban Planning and Construction, 2025)
The COVID-19 pandemic exposed deep-seated socio-economic and infrastructural vulnerabilities within urban slums, disproportionately affecting low-income communities in developing countries. In Nigeria, systemic challenges such as underfunded healthcare, limited social protection, and widespread poverty intensified the crisis for urban poor populations. This study examines the impacts of the pandemic on slum dwellers in Enugu City, marked by overcrowding, poor sanitation, etc., and explores their adaptation strategies. The study adopted a mixed-method approach, combining questionnaires and interviews to elucidate information. Data was collected from 180 respondents and selected key participants across five Enugu slums. Analysis involved SPSS for quantitative data and thematic coding for qualitative insights. The study reveals that the COVID-19 pandemic had significant social, economic, and environmental impacts on slum dwellers in Enugu Urban. Socially, residents faced increased poverty, crime, and marginalization, but relied heavily on local support for survival. Economically, job losses, rising costs, and restricted mobility deepened hardship. Despite these challenges, slum dwellers demonstrated resilience through adaptive practices like digital business, farming, and mutual support. Drawing lessons from these adaptive responses, the paper highlights the need for inclusive, context-sensitive urban policies that strengthen the resilience of informal settlements and promote sustainable development in pandemic preparedness and urban planning frameworks.